Splenic abscess in children: A report of three patients - Rattan Kamal; Kadian Yogender; Saroha Vikas; Jindal Nipun (Wolters Kluwer Medknow Publications, 2009)
Splenic abscess is uncommon in paediatric age group. It usually occurs in conditions of disseminated infective focus. Conventional treatment of abscess is incision and drainage, although splenectomy or splenic conservation is alternative. In this report, we are presenting case summaries of three patients suffering from splenic abscess. A retrospective review of three children was managed for eplenic abscess in our institution.All three patients presented with pyrexia, weight loss, and recurrent abdominal pain for more than six weeks. Human immunodeficiency virus (HIV) antibody detection test (ELISA) was nonreactive in all of them. The first patient was managed by splenectomy because of multiple splenic abscesses involving the entire spleen; the second one had exploratory laparotomy and drainage of splenic abscess with preservation of the spleen; and the third patient had successful ultrasonic guided aspiration of abscess. The follow-up ultrasonography done after three and six months in two patients, with splenic conservation, did not reveal any recurrence of abscess. In children with splenic abscess, ultrasound guided aspiration of abscess should be the first line of treatment, when this fails either because of multiple abscesses or dense adhesions around the spleen then splenectomy or open drainage may become necessary.